Nd:YAG Laser Vitreolysis for Symptomatic Vitreous Floaters: Application of Infrared Fundus Photography in Assessing the Treatment Efficacy - Xiaolei Sun; Jingyi Tian; Jinyan Wang; Jingjing Zhang; Ying Wang; Gongqiang Yuan (Journal of Ophthalmology)
Background. Vitreous floater is a physically common phenomenon with aging and is related to visual impairment and decrease of quality of life. Nd:YAG vitreolysis is supposed to be an option for resolving floaters, but its clinical efficacy is undefined. We aimed to evaluate the efficacy of Nd:YAG vitreolysis in treating floater semiquantifiably by determining changes of floater areas on infrared fundus photography (IR). Methods. Patients with floaters and those who underwent Nd:YAG vitreolysis were retrospectively summarized from June 2015 to Nov 2017. Intraocular pressure, visual acuity, visual function questionnaire (VFQ-25) scores, and floater areas calculated using Image J software were recorded preoperatively and 6 months after YAG lasers. Results. 50 patients (25 female/25 male, with an average age of 60.34 years) with 55 eyes (29 OD and 26 OS) presenting floaters and underwent YAG vitreolysis treatment were included. Severe symptoms were reported in 17 eyes, moderate in 21 and mild in 17 eyes. No severe Nd:YAG vitreolysis procedure-related complications occurred in all patients except one mild retinal injury. There were no significant changes in intraocular pressure and visual acuity after the laser treatment. 43 eyes had improved symptoms; in 8, floaters had disappeared; and 4 had no changes according to VFQ-25 scores. The median of shadow areas of floaters before operation was 1.41 (0.29–12.85) cm2, which decreased to 0.12 (0–2.77) cm2 after the operations (t=5.849,  P=0.001). The mean VFQ-25 scores increased to 88.54 ± 12.74 from the baseline 71.44 ± 12.77 (t=11.82,  P=0.001). Pearson correlation analysis showed that the shadow areas of floaters were negatively correlated to VFQ-25 scores before (r=−0.73,  P=0.001) and after (r=−0.72,  P=0.001) treatments. Conclusion. Nd:YAG vitreolysis was effective and safe in alleviating the visual symptoms induced by floaters. Quantification of floater shadow areas on infrared fundus photography could serve as an objective index for assessing treatment efficacy of Nd:YAG vitreolysis.